1987
DOI: 10.1128/iai.55.9.2240-2246.1987
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of monoclonal antibodies to evaluate the involvement of Campylobacter jejuni in proliferative ileitis in Syrian hamsters (Mesocricetis auratus)

Abstract: The role of Campylobacterjejuni in the pathogenesis of proliferative ileitis in Syrian hamsters was evaluated with monoclonal antibodies of different specificities. Monoclonal antibodies were produced with two different specificities: one for all members of the genus Campylobacter tested (antibody 8322-2E6) and one for C. jejuni and Campylobacter coli (antibodies 841-2A11, 841-4C6, and 841-5B1). Ileal sections from healthy hamsters, from hamsters with naturally occurring proliferative ileitis, and from hamster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…The organism continued to multiply in the original cell cultures (with additional 2:1 splittings on days 14, 18, and 20) through day 19 ml of infected supernatant per 25-cm2 surface area). During the first five passages in cell culture, intracellular organisms could be detected by phase microscopy within 72 h of infection, with the interval between infection and microscopic detection decreasing in later passages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organism continued to multiply in the original cell cultures (with additional 2:1 splittings on days 14, 18, and 20) through day 19 ml of infected supernatant per 25-cm2 surface area). During the first five passages in cell culture, intracellular organisms could be detected by phase microscopy within 72 h of infection, with the interval between infection and microscopic detection decreasing in later passages.…”
Section: Resultsmentioning
confidence: 99%
“…Proliferative ileitis (transmissible ileal hyperplasia, wet tail) is a serious infectious disease of hamsters characterized by hyperplasia of the ileal epithelium and pyogranulomatous inflammation. Light microscopic studies have revealed a gram-negative, slightly curved bacillus within the hyperplastic ileal epithelial cells (6)(7)(8)19). Ultrastructurally, the intracellular bacterium resembles members of the genus Campylobacter (2,9,20).…”
mentioning
confidence: 99%
“…Intracellular Campylobacter-like organisms in lesions of hamsters with proliferative enteritis have been reacted previously with monoclonal antibodies to C. jejuni with negative results, suggesting that the intracellular organisms were distinct from recognized Campylobacter spp. (27). However, that study did not include antibodies specific to the intracellular organisms.…”
Section: Antigensmentioning
confidence: 99%
“…We have previously reported the presence of intracellular Campylobacter-like organisms in normal hamsters (15,16). These organisms were demonstrated during immunofluorescence studies with a monoclonal antibody that has consistently recognized all Campylobacter species tested.…”
mentioning
confidence: 94%
“…Light and electron microscopic studies of ileal sections from hamsters with proliferative ileitis (4,7,17) have also implicated members of the genus Campylobacter. Recent studies, however, have suggested that C. jejuni is only minimally involved in the pathogenesis of proliferative ileitis and that other members of the genus Campylobacter may be involved (15,16).…”
mentioning
confidence: 99%